Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set: 121

Answer

$z^{10}\sqrt[3] (z^{2})$

Work Step by Step

$\sqrt[3] (z^{32})=\sqrt[3] (z^{30}\times z^{2})=\sqrt[3] (z^{30})\times \sqrt[3] (z^{2})=z^{10}\sqrt[3] (z^{2})$ We know that $\sqrt[3] (z^{30})=z^{10}$, because $(z^{10})^{3}=z^{10\times3}=z^{30}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.